The effect of nurses’ individual and occupational characteristics and perceptions of hierarchical career plateau on their turnover intention: A cross-sectional study - Şehrinaz Polat; Tuğba Yeşilyurt Sevim; Hanife Tiryaki Şen (PLoS ONE, 2025)
Career plateau is associated with undesirable work outcomes such as low job performance, motivation, work and organizational commitment, increased counterproductive work behaviors, and turnover intentions. The aim of the present study was to examine the effect of nurses’ personal and professional characteristics and their perceptions of hierarchical career plateau on their turnover intentions. Hierarchical plateaus refer to points within an organization’s pyramidal structure where opportunities for career advancement become limited or cease entirely. Experiencing a career plateau can result in negative work outcomes, including decreased job satisfaction and reduced motivation. This cross-sectional study was conducted from March to June 2024 with 464 nurses working in hospitals across Türkiye. Participants were selected using a convenience sampling method. Data were collected using a Nurse Information Form, the Career Plateau Survey and Turnover Intention Scale. Multivariate linear regression analysis was used to determine the effect of independent variables (individual and occupational characteristics and perceptions of hierarchical career plateau) on the dependent variable (turnover intention). This study was conducted in accordance with the STROBE checklist for cross-sectional studies. The findings indicated that nurses’ turnover intention increased as the level of hierarchical career plateau increased. Additionally, nurses working in private/non-profit healthcare organizations who had voluntarily chosen their profession exhibited statistically significantly lower turnover intentions. Interventions aimed at reducing career plateaus, tailored to the type of healthcare institution, and supporting nurses’ autonomy in career choice can reduce turnover intentions. It is recommended to regularly review promotion policies in healthcare institutions to align with the needs and expectations of current nurses, and to implements programs specific to their career development.